Concise Review: Role of DEK in Stem/Progenitor Cell Biology123. (23rd August 2013) - Broxmeyer, Hal E.; Mor‐Vaknin, Nirit; Kappes, Ferdinand; Legendre, Maureen; Saha, Anjan K.; Ou, Xuan; O'Leary, Heather; Capitano, Maegan; Cooper, Scott; Markovitz, David M.
Abstract Understanding the factors that regulate hematopoiesis opens up the possibility of modifying these factors and their actions for clinical benefit. DEK, a non‐histone nuclear phosphoprotein initially identified as a putative proto‐oncogene, has recently been linked to regulate hematopoiesis. DEK has myelosuppressive activity in vitro on proliferation of human and mouse hematopoietic progenitor cells and enhancing activity on engraftment of long‐term marrow repopulating mouse stem cells, has been linked in coordinate regulation with the transcription factor C/EBPα, for differentiation of myeloid cells, and apparently targets a long‐term repopulating hematopoietic stem cell for leukemic transformation. This review covers the uniqueness of DEK, what is known about how it now functions as a nuclear protein and also as a secreted molecule that can act in paracrine fashion, and how it may be regulated in part by dipeptidylpeptidase 4, an enzyme known to truncate and modify a number of proteins involved in activities on hematopoietic cells. Examples are provided of possible future areas of investigation needed to better understand how DEK may be regulated and function as a regulator of hematopoiesis, information possibly translatable to other normal and diseased immature cell systems. STEM Cells2013;31:1447–1453